Teaching the Digital Generation : No More Cookie-Cutter High Schools. - Kelly, Frank S. (SAGE Publications, 2008)
The authors show how traditional industrial-type high schools have failed to meet students' learning needs and explore ten alternative high school models that address 21st-century skills.